Characterisation of five alcohol dehydrogenases from Lactobacillus reuteri DSM20016. (November 2019) - Hu, Zhenghong; Jia, Pu; Bai, Yajun; Fan, Tai-ping; Zheng, Xiaohui; Cai, Yujie
Graphical abstract: Highlights: These alcohol dehydrogenases can catalyze various aldehydes with aromatic odors. Temperature, pH properties of these enzymes were described. These enzymes properties contributed to cheese ripening and flavor formation. Abstract: Alcohol dehydrogenases convert aldehydes causing volatile aromas in cheese into corresponding alcohols. In this study, we cloned and recombinantly produced five novel ADHs from Lactobacillus reuteri DSM20016 in Escherichia coli BL21 (DE3). The resulting proteins have molecular weights between 35 and 39 kDa. The optimum pH for enzyme activity of ADH-1, ADH-2 and ADH-3 was weakly acidic (pH 5, 6 and 5, respectively), compared with pH 7 for ADH-4 and ADH-5. The optimum temperature range for ADH-1, ADH-3, ADH-4 and ADH-5 was 40 °C ―55 °C, compared with 35 °C for ADH-2. These enzymes reduced a broad range of substrates; the highest catalytic efficiency and substrate affinity for ADH-1 was observed with heptaldehyde (Kcat /Km  = 39.4 s −1 ·mM −1, Km  = 0.459 mM), while 3-methylbutanal was the best substrate for ADH-5 (Kcat /Km  = 24.0 s −1 ·mM −1, Km  = 1.35 × 10 −2  mM). ADH-2, ADH-3 and ADH-4 exhibited the highest substrate affinity for valeraldehyde, propionaldehyde, and hexanal, respectively (Km  = 1.19 × 10 −2  mM, 2.81 × 10 −2  mM, 1.35 × 10 −2  mM). The enzymatic properties indicated that these enzymes effectively converted fragrant compounds during cheese ripening.